Self-Selection and the Probability of Quitting: A Contracting Approach to Employee Turnover in Public Accounting - Waller, William S. (Journal of Accounting Research, 1985)
William S. Waller, Self-Selection and the Probability of Quitting: A Contracting Approach to Employee Turnover in Public Accounting, Journal of Accounting Research, Vol. 23, No. 2 (Autumn, 1985), pp. 817-828